Pain relief during labor and parturition: introductory note - Helenna Vieira Schvartz; Andrêssa Batista Possati; Lisie Alende Prates; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2016)
Aim: to know the experience of mothers in relation to pain relief during labor and delivery. Method: field study of qualitative approach and descriptive focus. The setting of the study will be a Basic Health Unit. The survey participants will be mothers who have experienced childbirth up to six months before the development of the study. Data will be collected through semi-structured interviews, and, then, analyzed by the operative proposal. Expected results: to promote discussions and reflections for professionals and health institutions about the use of pain relief strategies during labor and delivery, and also to contribute to the quality of the care provided to the parturient in labor and delivery.